Habituation of the Mutual Cooperation Character in Pancasila Education in Elementary Schools - Zakiya, Aliya; Santoso, Gunawan (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research aims to analyze the strengthening of the character of mutual cooperation in Pancasila education learning in class V of SDN Pondok Betung 04. Strengthening the character of mutual cooperation is an important aspect of character education which is expected to shape students into individuals who have social awareness and the ability to work together in life. daily. Design/methodology/approach: The research method used is a case study with a qualitative approach, involving classroom observations, in-depth interviews with teachers and students, as well as analysis of documentation related to learning implementation plans (RPP) and teaching materials. Findings: The results of the research show that the initial condition of the mutual cooperation character of class V students at SDN Pondok Betung 04 still needs to be improved. Several effective methods and strategies in learning Pancasila Education to strengthen the character of mutual cooperation include project-based learning, group discussions and collaborative activities. The effectiveness of these methods and strategies can be seen from increasing students' ability to work together, help each other, and participate actively in class activities. However, this research also found several inhibiting factors, such as limited time, lack of parental involvement, and lack of supporting resources. The role of teachers and the school environment is very important in supporting the strengthening of the character of mutual cooperation, especially through modeling behavior and providing motivation to students. Positive responses from students and parents show that this program was well received and had a positive impact on student character development. Based on these findings, this research recommends increasing training for teachers on character learning methods, increasing parental involvement, and providing adequate resources to support character strengthening programs. In this way, it is hoped that strengthening the character of mutual cooperation can be more effective and sustainable in learning Pancasila Education at SDN Pondok Betung 04. Paper type: Research paper